Penelitian Pendahuluan Bioekologi Ikan Terubuk di Perairan Bengkalis, Riau - Thamrin Thamrin (Universitas Riau, 2019)
Terubuk (Tenualosa macrura)is an endangered and under protected species in Riau Province. A series survey activity was conducted at least one time in a week (in May to November 2016) at Bengkalis regency waters for knowing the development of gametes and fish oocytes. However, the survey activities were not carried out in June to August. The result shows that the T. macrura was not spawning simultaneously among individuals; however when removing eggs and sperm were carried out simultaneously or totally released between oocytes and sperm, with the most spawning occurs in September each year.